Smart Waste Management: A Conceptual Design and Analysis of GIS Based Real Time Waste Management using Mobile Application - Abdul Saboor Osmani, Sayed; Ambrish, G (International Journal of Computer Sciences and Engineering, 2020)
One of the major pollutants of environment is waste, if it is not managed and controlled, it will cause health hazards and increase environmental pollution. Nowadays we observe much improvement in technology, most of the developed countries manage the waste using smart systems and automated machines. Some countries still use the traditional waste management system. Due to rapidly increasing of population, huge amount of waste is generated daily. Traditional waste management system has some drawbacks and problems, for instance, producer maintains the waste as mixed and collector also collects as mixed. There is no monitoring system on producer and collector, some producers throw the garbage around the trash bins, some collectors even do not collect the waste, so neither producer and nor collector do their job properly. To overcome the problems and manage wastes efficiently, this paper has proposed online (Geographic Information System) GIS based mobile application system. The producers and collectors of waste are monitored through online platform and requests the producers to maintain biodegradable and non-biodegradable wastes separately. Using mobile application, producer requests the system for collection of waste, meanwhile the system assigns the task to collector which is near to producer’s location. The collector reaches to the location through the best path and collects the wastes as separate. Additional features and functionalities of the system also discussed in this paper.